2019
DOI: 10.3389/fphar.2019.00349
|View full text |Cite
|
Sign up to set email alerts
|

Phthalimide Derivative Shows Anti-angiogenic Activity in a 3D Microfluidic Model and No Teratogenicity in Zebrafish Embryos

Abstract: Angiogenesis is a crucial event for tumor progression and metastasis. It is the process through which new blood vessels are formed and has become a therapeutic target in many cancer therapies. However, current anti-angiogenic drugs such as Thalidomide still have detrimental teratogenic effects. This property could be caused by the presence of chiral carbons, intrinsic to such compounds. We synthesized four different phthalimide derivatives that lack chiral carbons in their chemical struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…[25][26][27] 3D microfluidic models allow a real-time analysis of cellular interactions, the possibility to mimic the main steps of the metastatic cascade and elucidate critical factors in the tumor progression. [28][29][30][31][32][33] For instance, the involvement of macrophages in regulating the intravasation of breast cancer cells through an endothelial layer when co-cultured in a microfluidic device was demonstrated by Zervantonakis et al 34 In a microfluidic-based lung carcinoma model, Bai et al investigated the contribution of tumor-associated macrophages (TAMs) in modulating the epithelial-to-mesenchymal transition (EMT) of cancer cell aggregates. 35 Additionally, Penny et al showed that TAMs promote PDAC cell extravasation through a vascular wall by co-culturing cancer cells, macrophages and endothelial cells (ECs) in a microfluidic device.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] 3D microfluidic models allow a real-time analysis of cellular interactions, the possibility to mimic the main steps of the metastatic cascade and elucidate critical factors in the tumor progression. [28][29][30][31][32][33] For instance, the involvement of macrophages in regulating the intravasation of breast cancer cells through an endothelial layer when co-cultured in a microfluidic device was demonstrated by Zervantonakis et al 34 In a microfluidic-based lung carcinoma model, Bai et al investigated the contribution of tumor-associated macrophages (TAMs) in modulating the epithelial-to-mesenchymal transition (EMT) of cancer cell aggregates. 35 Additionally, Penny et al showed that TAMs promote PDAC cell extravasation through a vascular wall by co-culturing cancer cells, macrophages and endothelial cells (ECs) in a microfluidic device.…”
Section: Introductionmentioning
confidence: 99%
“…Currently microfluidic systems have been used to culture various small organisms such as zebrafish [139,140], C. elegans [141,142] and fruit flies [143]. Despite that some of these models have been applied for chemical evaluations [144,145,146], few have been adopted in NP evaluation. C. elegans is one of the model organisms which have been applied for NP testing.…”
Section: Key Microfluidic Models For Np Evaluationmentioning
confidence: 99%
“…Many studies have attempted to mimic the angiogenic tumor microenvironment using microfluidic devices. One such device was used to show the role of phthalimide compounds in reducing angiogenesis by observing the sprouting ability of endothelial cells after treatment (Mercurio et al 2019 ). Treatment of tumor organoids with tyrosine kinase inhibitor sorafenib showed a disturbance in the formation of endothelial networks.…”
Section: Introductionmentioning
confidence: 99%